Hubungan Kompetensi Kepribadian Guru Terhadap Minat Belajar Pendidikan Agama Islam di SMAN 94 Jakarta Barat - Zubairi, Zubairi; Nurdin, Nurdin; Mulyawan, Asep; Ajizah, Siti Nur (LP. Ma'arif Janggan Magetan, 2024)
This research aims to determine the relationship between teacher personality competence and interest in learning PAI at SMAN 94 West Jakarta. The hypothesis tested is that there is a relationship between teacher personality and interest in learning PAI at SMAN 94 West Jakarta. This research was conducted using the Correlation method with descriptive quantitative analysis. The target population is all class XI students at SMAN 94 West Jakarta, totaling 216 students. The samples taken used a quota sampling technique, namely 35 students in class XI MIPA 3. This research instrument uses a questionnaire to measure teacher personality competence regarding interest in learning PAI. From the results of the questionnaire items arranged at intervals, it was obtained that the percentage level of teacher personality competence was categorized as good at 84% taken from the answers strongly agree and agree and interest in learning PAI was categorized as good (see table 9) with a percentage level of 73% taken from the answers strongly agree and agree. Meanwhile, from hypothesis testing it can be concluded that there is a very close or very strong relationship between teacher personality competence and interest in learning PAI. This is shown by the correlation coefficient rxy = 0.902 with a determination coefficient of 0.813. This means that the personality competence of PAI teachers contributes 81.3% to the interest in learning PAI class XI MIPA 3 at SMAN 94 West Jakarta. It is hoped that the results of this research will be useful for improving the quality of teachers' personality competencies in order to improve student learning outcomes, especially in PAI subjects. Besides that, the results of this research can be used as a reference by related agencies in providing references to teachers' personality competencies in teaching so that they will increase students' interest in learning later.